If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 + -4 = 12 Reorder the terms: 5 + -4 + x = 12 Combine like terms: 5 + -4 = 1 1 + x = 12 Solving 1 + x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 12 + -1 Combine like terms: 1 + -1 = 0 0 + x = 12 + -1 x = 12 + -1 Combine like terms: 12 + -1 = 11 x = 11 Simplifying x = 11
| -5(2p+2)-28=3(4p+2) | | (x-7)(2x-11)= | | -8(-11h-9)=-16+4(19h-20) | | 4(10-x)=64 | | 3=3(s+4) | | -63+12y+3=5(3y-5)-8 | | 20d+-4=16 | | a-3.2=55 | | -75=-5(5+2n) | | 7(c-2)+6=3+c-11 | | -3+12t=-7 | | 2(x+3)-4(3x-1)+6-(5x-2)+3x=0 | | 15=3+-3n | | 106=-8k+6 | | 0.40x+0.27y= | | .8y-8=.4+16 | | 4(8m-7n)+6(3n-4m)= | | 16x-31=33 | | 6(2n-4)=-72 | | 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 |